(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: The relationship between systemic arterial blood pressure (BP) and carotid artery diameter is often derived from hypertensive cohorts. This study explores this relationship in a normotensive Nigerian population to understand vascular physiology in the absence of pathology. Methods: We analyzed data from 104 healthy adults. Carotid artery diameters were measured via ultrasonography. Pearson's correlation and ANOVA were used to assess relationships with systolic blood pressure, diastolic blood pressure and their mean arterial pressures (MAP). Results: Mean age of the cohort was 28 years. In the overall cohort, correlations between BP and carotid diameter were largely absent or weak. A sex-stratified analysis revealed a distinct pattern: in females, there were significant positive correlations between MAP and the right ECA (r=0.453, p=0.003) and left ECA (r=0.335, p=0.030). No significant correlations were observed in males at all. No correlations existed between the larger common and internal carotid arteries with blood pressure parameters Conclusion: The relationship between arterial blood pressure and carotid artery diameter in healthy, normotensive individuals is weak and exhibits sexual dimorphism, being evident only in females. This suggests that the strong correlations reported in literature are likely a feature of pathological hypertensive remodeling rather than normal physiology. The female-specific association warrants further investigation.